No effect of eccentric training on jumper's knee in volleyball players during the competitive season: A randomized clinical trial - Visnes, H.; Hoksrud, A.; Cook, J.; Bahr, R. (Clinical Journal of Sport Medicine, 2005)
Background: The effect of surgery on patellar tendinopathy (jumper's knee) is questionable, and conservative treatment protocols have not been properly documented.